Ubuntu on a Dime The Path to Low-Cost Computing - Kelly, James Floyd (Apress, 2013)
Are you ready to do the same thing? Have you decided that a new computer would be nice? How about a new computer that has inside what you want at the price you decided on? If this sounds great to you, welcome to Ubuntu on a Dime. You’ll have fun, save some money, learn a new skill, and end up with a whiz-bang new PC to brag about. Don’t believe me? Keep reading. I dare you.